Cloud-Integrated Automated Dosing System for pH and Nutrient Control in NFT Hydroponics Using ThingSpeak - Bista, Rejina; Bista, Abhinav; Bhattarai, Binita; Ghimire, Sandeep Raj (International Journal on Engineering Technology and Infrastructure Development, 2026)
Hydroponics is a modern agricultural technique in which plants are cultivated in nutrient rich water instead of soil. With increasing urbanization and the reduction of fertile agricultural land in Nepal, there is a growing need for efficient and sustainable farming technologies. The study presents the design and implementation of a cloud-integrated automated dosing system for pH and nutrient control in a Nutrient Film Technique (NFT) hydroponic setup using Internet of Things (IoT) technology and the ThingSpeak cloud platform. The developed system consists of an ESP32 microcontroller integrated with pH, Total Dissolved Solids (TDS), and DHT11 sensors for real-time monitoring of water quality and environmental parameters. Sensor data serve as the primary data source and are continuously uploaded to the ThingSpeak cloud for remote visualization and analysis. A rule-based automated control algorithm was implemented to maintain optimal pH and nutrient concentrations. Based on sensor feedback, dosing pumps were activated using pre-defined threshold values and timed dosing cycles to automatically adjust pH and TDS levels. pH sensor calibration was performed using standard buffer solutions and validated through regression analysis against measurements obtained from a digital pH meter. Experimental results demonstrated reliable system performance, with the pH sensor achieving a coefficient of determination (R²) of 0.9862 indicating a strong correlation between sensor readings and reference measurements. The automated dosing mechanism successfully maintained water quality parameters within the desired range, while hydroponically grown plants exhibited faster growth, healthier root development and higher yield compared to conventionally cultivated soil-based plants. The integration of ThingSpeak enabled effective cloud-based monitoring and data logging supporting remote management of the hydroponic system. The findings indicate that the proposed IoT enabled automated hydroponic system is a cost-effective and efficient solution for precision agriculture, particularly in urban and land-constrained environments.